The Inhibitory Effect of Cinnamon (Cinnamomum zeylhnicum) and Ginger (Zingiber officinal) in the Growth of Some Bacterial Species in the Gastrointestinal Tract of the Quail: Husam H. Nafia,BaKer T. Jaber and Nuha I. Hasan - Nafia, Husam H. (The Iraqi Journal of Veterinary Medicine, 2012)
This experiment conducted for studying the effects of crushed cinnamon and ginger to the diet at levels 0.1, 0.3, 0.6% in the bacterial growth of gastrointestinal tract of the quail. Ninety birds one day age divided randomly into ten transactions as 9 birds per treatment (three birds per duplicate). The numbers of bacteria, total aerobic bacteria in the colon of feces of birds were calculated, the results showed a significant reduction in the number of aerobic bacteria and the numbers of bacteria in the colon. Proportionally increase in the levels of crushed cinnamon, ginger, individually or in combination in comparison the control group showed influence inhibitory to the numbers of bacteria in the colon and aerobic bacteria when you add different levels of transactions compared to crushed ginger and cinnamon mixture into the bush.